2019
DOI: 10.1096/fj.201802617r
|View full text |Cite|
|
Sign up to set email alerts
|

New insight into the classification and evolution of glucose transporters in the Metazoa

Abstract: Because glucose is an essential energy source for living organisms, glucose transporters (GLUTs) are present in all species worldwide. Encoded by the solute carrier family 2 gene family, the GLUT proteins generally have 12 transmembrane helices (TMHs). In total, 14 GLUT proteins have been identified in humans (hGLUTs), and they are divided into 3 classes on the basis of their transport characteristics and sequence similarities. Herein, we report the use of protein sequence similarity networks (SSNs) to visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous SSN studies of glycyl radical enzymes and transporters have suggested that proteins in each cluster of an SSN share a similar biochemical activity; 26,27 however, this conclusion does not seem to apply to BSH clusters. The enzymes in Cluster 2 have been well-studied.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous SSN studies of glycyl radical enzymes and transporters have suggested that proteins in each cluster of an SSN share a similar biochemical activity; 26,27 however, this conclusion does not seem to apply to BSH clusters. The enzymes in Cluster 2 have been well-studied.…”
Section: Discussionmentioning
confidence: 92%
“…Although the SSN methods are based on sequence identities from BLAST bit-scores, which is different from sequence alignments in phylogenetic analyses, previous studies have shown that SSNs serve as a visually useful tool to reveal sequence-structurefunction associations and evolutionary relationships between protein families. 25,26 In case of BSHs, previous studies have classified BSHs into three, four, or eight clusters based on phylogenetic analysis; however, these analyses were based on <400 protein sequences. [15][16][17] Song et al grouped BSHs into eight clusters using phylogenetic analysis, but the classification separated several BSHs with high sequence identity into different clusters, 17 which led to overclassification.…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated until no newer putative BaiE sequences were found. The SSNs of all query and identified protein sequences were generated using EFI-EST with an alignment score of 70 and visualized using Cytoscape v.3.3 ( 63 ), as described previously ( 64 ).…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance is characterized by defects of insulin signaling and reduction of glucose uptake in peripheral insulin-sensitive cells or tissues. Glucose uptake, a highly regulated process mediated by cell surface localization of glucose transporters (GLUTs) [ 33 ], is important for the survival and growth of endothelial cells, due to its reliance on glycolysis as an energy source [ 34 ]. Interestingly, HUVECs lack the expressions of GLUT2, GLUT4, and GLUT5 mRNA [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%